On the spatial coherence of rainfall over the Saloum delta (Senegal) from seasonal to decadal time scales - WADE, Malick; Mignot, Juliette; Lazar, Alban; Gaye, Amadou Thierno; Carré, Matthieu (Frontiers in Earth Science, 2015)
A paleoreconstruction of the length and intensity of the rainy season over western Africa has been recently proposed, using analysis of fossil mollusk shells from the Saloum delta region, in western Senegal. In order to evaluate the significance of local long-term reconstructions of precipitations from paleoclimate proxies, and to better characterize the spatial homogeneity of rainfall distribution in northern Africa, we analyze here the spatial representativeness of rainfall in this region, from seasonal to decadal timescales. The spatial coherence of winter episodic rainfall events is relatively low and limited to surrounding countries. On the other hand, the summer rainfall, associated with the West African Monsoon, shows extended spatial coherence. At seasonal timescales, local rainfall over the Saloum is significantly correlated with rainfall in the whole western half of the Sahel. At interannual and longer timescales, the spatial coherence extends as far as the Red Sea, covering the full Sahel region. This spatial coherence is mainly associated to the zonal extension of the Inter Tropical Convergence Zone. Coherently, summer rainfalls appear to be driven by SST anomalies mainly in the Pacific, the Indian Ocean, the Mediterranean basin, and the North Pacific. A more detailed analysis shows that consistency of the spatial rainfall coherence is reduced during the onset season of the West African Monsoon.